Perbandingan Stok Karbon Mangrove Rhizophora mucronata di Kampung Enggros dan Entrop, Jayapura, Papua. - Muhammad Hisyam; Ervina Indrayani; John D Kalor; Ida Waum (Cenderawasih University, 2023)
Mangrove ecosystems have an important role as a filter for CO2 gas that is in the air through the process of photosynthesis. This is why the existence of mangrove forests is of great concern in maintaining the carbon cycle in the world. Most of the mangrove forests in Indonesia are in the Papua region, which accounts for one-third of the total area of mangrove forests in Indonesia. One of the mangrove forest areas that is quite thick is in the Youtefa Bay area in Enggros and Entrop Villages with Rhizophora mucronata species found. This research was conducted by measuring the carbon content using an allometric formula that utilizes stem diameter values. This study showed that the biomass of Rhizophora mucronata in Entrop Village was more than that of Enggros Village, which was 1063.44 Kg. Carbon content and absorption also showed results that were directly proportional to the biomass in Entrop Village at 19.4616 and 71.42 Kg/m2. The ratio of the difference in biomass and carbon content between the two villages also shows a difference of 14%.